(untitled) (Berlin, 2005)
This book constitutes the thoroughly refereed postproceedings of the First International Workshop on Semantic Web Services and Web Process Composition, SWSWPC 2004, held in San Diego, CA, USA in July 2004.
Keywords: Dịch vụ Mạng,Semantic Web,Web services,World Wide Web,Mạng Ngữ nghĩa học,Mạng toàn cầu